Disability did not prevent Nor Shafiqah and Nabil Lutfi from achieving their dreams - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 8 November 2022 – Being disabled and possessing a Person With Disability (PWD) card do not prevent students from pursuing further education at the university or having a career.